A discourse analysis of lecturer’s spoken language in english class of STIKES Eka Harap Palangka Raya - Roliani, Chintia Monica (Indonesia Berdaya, 2024)
The objective of this research were: (1) Analyze the lecturer use English instruction (refer to Lesson Plan) of STIKES Eka Harap Palangka Raya in the Academic Year 2023/2024. (2) Analyze the structure use by the lecturer of STIKES Eka Harap Palangka Raya in the Academic Year 2018/2019. (3) Analyze the vocabulary use by the lecturer of STIKES Eka Harap Palangka Raya in the Academic Year 2018/2019. The research was conducted using qualitative research Methods. One English lecturer of STIKES Eka Harap Palangka Raya was the subject of the study. The data were from observation class and interviews the lecturer. The result of data analysis and the discussion of the findings we can conclude several matters related to the lecturer’s spoken language in the English class of STIKES Eka Harap Palangka Raya, as follows: (1) The lecturer’s use of English Instruction appropriate Lesson Plan, there are when orientation, apperception, motivation, and giving references. (2) The lecturer use a pattern of English spoken language at first and then followed by Indonesian, because of the students’ weakness in English. (3) The lecturer uses vocabulary with students as helper techniques can solve the problem. It has two advantages: first, make the condition of the classroom alive and give relaxing atmosphere, the second advantage is make the words easily stay in the students mind.